Bionomics of Eublemma amabilis Moore (Lepidoptera: Noctuidae), a Major Predator of Lac insect and Its Control Measure - Rahman, M Matiur; Ahmed, KN; Karim, KN Shahjahan; Ali, M Sohrab (Bangladesh Journal of Scientific and Industrial Research, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The moth, Eublemma amabilis Moore is very destructive to lac insect and lac encrustation. The moth is generally white-pinkish in colour and it lays gray-white and round eggs, depressed in the centre. The newly hatched larva enters the lac insect either through one of the opening in the cell or by tunneling a hole through the encrustation. A single larva damages 42-50 matured cells prior to pupation. It completes six generation in a year and causes comparatively more injury to the "Kartki" crop than to the Baishaki crop. The morphological details of this predator were studied. Several natural enemies of E. amabilis have been recorded. Key words: Eublemma amabilis, Lac, Predator, Crop injury and Control measure. doi: 10.3329/bjsir.v44i1.2714 Bangladesh J. Sci. Ind. Res. 44(1), 57-64, 2009